2021
DOI: 10.3390/pharmaceutics13071059
|View full text |Cite
|
Sign up to set email alerts
|

Antimelanogenesis Effects of Leaf Extract and Phytochemicals from Ceylon Olive (Elaeocarpus serratus) in Zebrafish Model

Abstract: The melanogenesis inhibition effect in zebrafish (Danio rerio) and antityrosinase activity of the ethanolic extract and its phytochemicals from Ceylon olive (Elaeocarpus serratus Linn.) leaves were investigated in this study. Among the leaf extract and four soluble fractions, the ethyl acetate soluble fraction exhibits the best antityrosinase and antimelanogenesis activities. One phenolic acid, gallic acid, and two flavonoids, myricetin and mearnsetin, are isolated from the active subfractions through the bioa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Gallic acid, gallotannin, valonia tannin and extracts of plants (e.g., Ceylon olive leaves and pomegranate peel) containing gallic acid exerted antimelanogenic effects directly by acting as a competitive inhibitor of tyrosinase and indirectly by inhibiting tyrosinase via antioxidant actions that affect melanogenesis pathway in vitro and in vivo ( Chen et al, 2009 ; Panich et al, 2013 ; Su et al, 2013 ; Kanlayavattanakul et al, 2020 ; Huang et al, 2021 ; Liu et al, 2021 ). A randomized, double-blind, placebo-controlled clinical trial demonstrated that continuous administration of apple polyphenol rich in procyanidins for 12 weeks improved UV-induced skin pigmentation in heathy women ( Shoji et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Gallic acid, gallotannin, valonia tannin and extracts of plants (e.g., Ceylon olive leaves and pomegranate peel) containing gallic acid exerted antimelanogenic effects directly by acting as a competitive inhibitor of tyrosinase and indirectly by inhibiting tyrosinase via antioxidant actions that affect melanogenesis pathway in vitro and in vivo ( Chen et al, 2009 ; Panich et al, 2013 ; Su et al, 2013 ; Kanlayavattanakul et al, 2020 ; Huang et al, 2021 ; Liu et al, 2021 ). A randomized, double-blind, placebo-controlled clinical trial demonstrated that continuous administration of apple polyphenol rich in procyanidins for 12 weeks improved UV-induced skin pigmentation in heathy women ( Shoji et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The structural determination of isolated compounds was performed by spectral analyses, including 1D NMR (Nuclear magnetic resonance spectroscopy) ( 1 H-NMR, 500 MHz; 13 C-NMR, 125 MHz) and 2D NMR (HSQC, HMBC, COSY, and NOESY) measured on a Bruker AVIII NMR spectrometer (Bruker Avance, Rheinstetten, Germany), FTIR (Fourier transform infrared spectroscopy, FTS-40, Bio-rad, Hercules, CA, USA), and MS (mass spectroscopy, MAT-958, Finnigan, MA, USA) [ 37 , 38 , 39 , 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…P. chinensis leaf essential oil (50 g) was further subjected to classical preparative silica gel column chromatography (CC) with a gradient elution of n -hexane and ethyl acetate of increasing polarity, and then separated into six fractions (E1–E6) using thin-layer chromatography (TLC) to analyze the elution profiles at both 254 nm and 365 nm UV light [ 41 , 42 , 43 ].…”
Section: Methodsmentioning
confidence: 99%